Fermentation of araticum, baru, and pequi by-products by probiotic strains: effects on microorganisms, short-chain fatty acids, and bioactive compounds - De Oliveira, Fellipe Lopes; Morzelle, Maressa Caldeira; Moretti, Marcia Maria De Souza [UNESP]; Casarotti, Sabrina Neves (Oxford University Press (OUP), 2023)
Fruit by-products, due to their unique chemical composition containing dietary fibers and bioactive compounds, may favor the growth of probiotic strains. This study evaluated the fermentation of araticum, baru, and pequi by-products using Lactobacillus acidophilus (La-5, LA3, and NCFM) and Bifidobacterium animalis subsp. lactis (Bb-12) probiotic strains. We assessed probiotic viability, short-chain fatty acid levels, and bioactive compound levels after 48 h of fermentation. Araticum and pequi by-products led to counts higher than 6 log CFU/mL after 48-h fermentation for all Lactobacillus strains, but only the araticum by-product supported the growth of the Bb-12 strain. Fermentation of araticum by-product resulted in greater amounts of acetate (39.97 mM for LA3 and 39.08 mM for NCFM) and propionate (0.20 mM for NCFM), while baru by-product showed greater amounts of butyrate (0.20 mM for La-5 and Bb-12). Fermentation of araticum and baru by-products resulted in an increase in bioactive compounds, with the latter showing total phenolic compounds and antioxidant activity from 1.4 to 1.7 and from 1.3 to 3.1 times higher, respectively, than the negative control treatment. Araticum by-product exhibited a higher potential for prebiotic effects, and fermentation by the tested probiotic strains is essential to increase bioactive compound levels. Significance and impact of the study Investigating the fermentation of fruit by-products by probiotic strains is valuable for understanding their prebiotic potential and reducing food waste. While previous research has focused on commonly utilized fruit by-products, little research has examined the fermentability of underexplored by-products from the Brazilian Cerrado. This is the first study to investigate the fermentation of araticum, baru, and pequi by-products by commercial probiotic microorganisms and the impact of fermentation on the probiotic viability, production of short-chain fatty acids, and bioactive compound levels. Furthermore, this study demonstrated that these fruit by-products are relevant sources of bioactive compounds and potential prebiotic ingredients.
Keywords: antioxidant; Bifidobacterium; fiber; fruit waste; Lactobacillus; phenolic compound